Problem of terminological determinants in structuring intercultural upbringing / education - is interculturalism in education possible when starting from "conflict or compromise between Islam and the Western culture"? - Tufekčić, Adnan (Zakład Pedagogiki Społecznej Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2016)
This article discusses the terminology used to define the current events in connection with the arrival of large number of people from Asian and African countries in the EU, which is also used to design the guidelines of intercultural education.
Keywords: terminological determinants; Islam; immigrants; identity; intercultural education